2022
DOI: 10.3390/microorganisms10030596
|View full text |Cite
|
Sign up to set email alerts
|

Biological Control of Plant Pathogens: A Global Perspective

Abstract: The increase in the world population has generated an important need for both quality and quantity agricultural products, which has led to a significant surge in the use of chemical pesticides to fight crop diseases. Consumers, however, have become very concerned in recent years over the side effects of chemical fungicides on human health and the environment. As a result, research into alternative solutions to protect crops has been imposed and attracted wide attention from researchers worldwide. Among these a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
156
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 334 publications
(230 citation statements)
references
References 204 publications
0
156
0
1
Order By: Relevance
“…Nevertheless, the use of only biopesticides is not ample to obtain higher crop productivity due to the complexity of the rhizosphere and the need to apply a high amount of these bioagents to cover the whole rhizosphere [26]. Lahlali et al (2022) [27] reported that the use of bioagents in crop protection systems is not always efficient to control plant pathogens. The authors explained their approach by the presence of several factors affecting the success of biological control against plant pathogens, such as the lack of studies under field conditions and the resistance of fungal pathogens to biofungicides.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of only biopesticides is not ample to obtain higher crop productivity due to the complexity of the rhizosphere and the need to apply a high amount of these bioagents to cover the whole rhizosphere [26]. Lahlali et al (2022) [27] reported that the use of bioagents in crop protection systems is not always efficient to control plant pathogens. The authors explained their approach by the presence of several factors affecting the success of biological control against plant pathogens, such as the lack of studies under field conditions and the resistance of fungal pathogens to biofungicides.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the growing importance of the biocontrol means, currently, several biocontrol agents are available on the market in the European Community, and others are in the evaluation stage for their approval by the EC authorities [152].…”
Section: Bcas Under Evaluation or Already Approved As Biofungicides I...mentioning
confidence: 99%
“…The strategies of biological control can be classified into conservation, importation, and augmentation according to the source of the deployed organisms [ 59 ]. The conservation strategy is carried out to maintain the existing natural enemies in an environment; the importation strategy is carried out to introduce exotic enemies of the pests where they do not occur naturally; and the augmentation strategy is carried out to release reared natural enemies periodically into the habitat where the pests occur [ 60 , 61 ].…”
Section: Control Strategies For Rknsmentioning
confidence: 99%